Seasonal variation of acute appendicitis - Mendoza-Rojas, Hubert James (2016)
Objective: To know if there was an increase in acute appendicitis cases treated in summer and spring among 2005-2014 in Grau Emergency Hospital in Lima. Material and Methods: Observational, cross-sectional and retrospective study. Non-probabilistic sampling, sample size of 6,917 operated on for acute appendicitis during 2005-2014 in the Grau Emergency Hospital in Lima. We used a form for data collection from medical records to develop a database. Analysis of variance test was applied to appendectomies numbers and correlation between temperature and number of appendicitis. Results: The minimum and maximum age was 14 and 93 years old. 52.6% (3,639) of the cases were female. January was the highest monthly number of appendectomies, with 648; 634 in March and 616 in February. The analysis of variance obtained a p value = 0.24, there was no significant difference among the seasons of the year. There was a partial correlation between monthly temperature and number of appendectomies. Conclusions: There is a seasonal pattern with increase in the frequency of acute appendicitis during summer and spring, and a decline in autumn and winter. The increase in cases of acute appendicitis is 3.32% and 3.75% in summer compared to autumn and winter, with no significant statistical difference among the four seasons of the year.